The influence of teachers' social competence on learning achievement at SDN Lebaksari, Sukabumi District - Siti Ulfah; Kun Nurachadijat (P3M IAI Nusantara Batang Hari, 2023)
This study aims to investigate the effect of teacher social competence on student achievement at SDN Lebaksari Kab. Sukabumi. The research sample involved 9 teachers and 50 students from various grade levels who were randomly selected. Data was collected through in-depth interviews as well as observation and documentation through school archives. The results of the data analysis indicate that there is a significant influence between the teacher's social competence and student achievement. The findings of this study indicate that teachers who have good social competencies, such as collaboration, communication, leadership, and empathy skills, play an important role in improving student achievement. This study also highlights several aspects that strengthen the effect of teacher social competence on student achievement. First, the teacher's social competence has an impact on creating an inclusive and conducive learning environment. Teachers who are able to create positive relationships with students encourage active participation in learning and a better understanding of the subject matter. Teachers who have good communication skills are able to involve parents in student learning, thereby providing additional support for student achievement. In conclusion, this study reveals that the social competence of teachers has a significant effect on student achievement at SDN Lebaksari Kab. Sukabumi. Therefore, increasing the social competence of teachers is important in improving student achievement. The implication of this research is the importance of supporting and developing teacher social competence in the context of education at SDN Lebaksari Kab. Sukabumi, with the aim of improving the quality of learning and student achievement as a whole.